Testing the muon g-2 anomaly at the LHC - Freitas, Ayres; Westhoff, Susanne (Arxiv, 2014)
The long-standing difference between the experimental measurement and the standard-model prediction for the muon's anomalous magnetic moment, $a_{μ} = (g_{μ}-2)/2$, may be explained by the presence of new weakly interacting particles with masses of a few 100 GeV. Particles of this kind can generally be directly produced at the LHC, and thus they may already be constrained by existing data. In this work, we investigate this connection between $a_{μ}$ and the LHC in a model-independent approach, by introducing one or two new fields beyond the standard model with spin and weak isospin up to one. For each case, we identify the preferred parameter space for explaining the discrepancy of a_mu and derive bounds using data from LEP and the 8-TeV LHC run. Furthermore, we estimate how these limits could be improved with the 14-TeV LHC. We find that the 8-TeV results already rule out a subset of our simplified models, while almost all viable scenarios can be tested conclusively with 14-TeV data.